Optimalisasi Sistem Pencarian Produk Sunscreen Melalui Rancangan Ontologi Semantik - I Gusti Agung Ayu Gita Pradnyaswari Mantara; I Komang Ari Mogi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
As a tropical country, Indonesia receives exposure to sunlight throughout the year which contains ultraviolet (UV) rays that are harmful to the skin. The use of sunscreen is important to protect the skin, but the lack of structured information regarding the characteristics of sunscreen makes it difficult to choose the appropriate product. This research aims to build an ontology model for a sunscreen product search system that is tailored to skin conditions using the Methontology method. In the implementation stage, the sunscreen ontology was developed with 1 class, 7 subclasses, 7 object property hierarchies, and 29 individuals using Protégé software. Evaluation is carried out by asking a SPARQL query that shows the ontology's ability to provide relevant answers according to the knowledge being modeled. This sunscreen product ontology model can be used as a basis for developing related knowledge management systems such as sunscreen product search systems.